Drinking water and domestic wastewater treatment: Maintenance, perceptions, and priorities - John A. Curtis (The Economic and Social Research Institute (ESRI), 2024)
The objective of this research is to capture householders' views and experiences related to drinking water and domestic wastewater treatment systems (DWWTS), including public health concerns and experience accessing the septic tank remediation grant. Capturing data on the level of maintenance undertaken by households with respect to their private drinking water supplies and DWWTS provides insight on the extent to which additional policy interventions are required to protect both public health and environmental quality.
Keywords: 330